209k views
5 votes
Using the given information, give the vertex form equation of each parabola.

Vertex: (4,-3) Focus:(47/12,-3)

User Rego
by
5.2k points

1 Answer

2 votes

Answer:

The equation of parabola is given by :
(x-4) = (-1)/(3)(y+3)^(2)

Explanation:

Given that vertex and focus of parabola are

Vertex: (4,-3)

Focus:(
(47)/(12),-3)

The general equation of parabola is given by.


(x-h)^(2) = 4p(y-k), When x-componet of focus and Vertex is same


(x-h) = 4p(y-k)^(2), When y-componet of focus and Vertex is same

where Vertex: (h,k)

and p is distance between vertex and focus

The distance between two points is given by :

L=
\sqrt{(X2-X1)^(2)+(Y2-Y1)^(2)}

For value of p:

p=
\sqrt{(X2-X1)^(2)+(Y2-Y1)^(2)}

p=
\sqrt{(4-(47)/(12))^(2)+((-3)-(-3))^(2)}

p=
\sqrt{((1)/(12))^(2)}

p=
(1)/(12) and p=
(-1)/(12)

Since, Focus is left side of the vertex,

p=
(-1)/(12) is required value

Replacing value in general equation of parabola,

Vertex: (h,k)=(4,-3)

p=
(-1)/(12)


(x-h) = 4p(y-k)^(2)


(x-4) = 4((-1)/(12))(y+3)^(2)


(x-4) = (-1)/(3)(y+3)^(2)

Using the given information, give the vertex form equation of each parabola. Vertex-example-1
User Petekaner
by
5.2k points